Pertanggungjawaban Pidana Korporasi oleh Pengurus dalam Kasus Karhutla Karena Unknown Cause: Perspektif Ekonomi dan Lingkungan - Aditya Wahyu Saputro; Rayhan Andyara Milono; Shafira Anna Medina (CV Rewang Rencang, 2021)
The punishment paradigm shift from retributive to restorative justice supports the principle of harmony and balance that emphasizes ecosystem conservation efforts for current and future generations. In the environmental sector, corporations are often involved in various environmental crimes such as forest and land fires. If forest and land fires causes are not known, it is necessary to construct criminal responsibility that is pro-environmental in form of mainstreaming damage recovery. This paper concludes that in the case of forest and land fires with an unknown cause, it is more appropriate to use corporate criminal mechanisms both from an economic and environmental point of view and the imposition of corporal punishment alone does not favor efforts to restore environmental damage.